Association Between Different Dietary Carbohydrate and Risk of Depression, Anxiety, and Stress Among Female Adolescents - Niayesh Naghshi; Asal N. Tehrani; Samira Rabiei; Vahideh Behrouz; Zahra Yari (International Journal of Preventive Medicine)
Purpose: Mental disorders account for a large part of the burden of disease in young population. The present study aimed to investigate the relationship between carbohydrate intakes and the risk of depression, anxiety, and stress among female adolescents. Methods: In this cross-sectional study, 263 female adolescents aged 15–18 years participated. Depression, anxiety, and stress scores were determined by DASS-21 (Depression Anxiety Stress Score-21 items) questionnaire, and dietary intakes were assessed using a validated 168-item food frequency questionnaire. Crude and multivariable-adjusted odds ratios (OR) and 95% confidence intervals (CIs) were estimated through logistic regression analysis. Results: Adolescents with depression consumed more glucose and sucrose and less lactose compared to adolescents without depression. After adjustment for all confounders, higher intakes of glucose and sucrose were significantly associated with increased risk of depression (OR glu = 1.3, P = 0.035 and OR suc = 1.41, P = 0.034), anxiety (OR glu = 1.3, P = 0.019 and OR suc = 1.81, P = 0.027), and stress (OR glu = 1.41, P = 0.046 and OR suc = 1.8, P = 0.044). In addition, increasing lactose intake was significantly associated with reducing the risk of depression (OR = 0.96, P = 0.013) and stress (OR = 0.96, P = 0.015). Conclusions: This study found significant associations between dietary carbohydrate intake and mental disorders among female adolescent.